Cross-Site Personalisation - Koidl, Kevin (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2014)
Web users are continuously confronted with vast amounts of information. This phenomenon is known as the information explosion and can lead to disorientation and decreased productivity as users attempt to navigate through information to discover what they need. Web Personalisation techniques, such as Adaptive Hypermedia, have been employed to overcome this issue. However, these techniques are typically focussed on closed collections of content, housed on a single website. This is at odds with the typical web browsing paradigm, where users navigate across multiple sites to identify relevant information. This thesis introduces the Cross-Site Personalisation (CSP) approach to Web Personalisation. This approach seamlessly personalises the support offered to each individual user as they browse across multiple websites. The approach models the user’s interactions and then tailors the information on each independent website to support their needs. The Cross-Site Personalisation approach is realised as a third-party personalisation service that interfaces with multiple websites via standard extension modules. The approach is non-intrusive and does not negatively impact on the user’s web browsing experience. It is also sensitive to the user’s privacy concerns by not divulging information about a user to the websites being personalised. Rather, this approach recommends how each website may adapt their information and navigation structures to meet the user’s needs. To evaluate the appropriateness of this approach two authentic use cases have been scoped, designed and developed. The first use case focuses on CSP within closed domains, such as those typically seen in enterprise website federations. The second use case addresses open domains, where the user is navigating across websites on the open web. This thesis details the State of the Art that underpins the Cross-Site Personalisation approach. It provides a detailed design and corresponding implementations that realise the two use cases. Furthermore, this thesis presents a thorough evaluation of the applicability and appropriateness of the approach in these authentic settings.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin.